1976
DOI: 10.1002/cjce.5450540107
|View full text |Cite
|
Sign up to set email alerts
|

On fluidized bed‐to‐surface heat transfer

Abstract: Development of new techniques has stimulated new interest in fluidized bed‐to‐surface heat transfer phenomena. In this paper a short critical review of major recent works on the subject as well as comments on the validity of some general concepts and of “small scale” equations available are presented. It appears that these concepts can serve as a basis for future development of reliable design equations for large commercial equipment and for analysis of its performance. Examples of the analysis of imperfectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…Key: symbols, seeTable I; -, Zabrodsky et al correlation(22)). Key: symbols, seeTable I; -, Zabrodsky et al correlation(22)).…”
mentioning
confidence: 99%
“…Key: symbols, seeTable I; -, Zabrodsky et al correlation(22)). Key: symbols, seeTable I; -, Zabrodsky et al correlation(22)).…”
mentioning
confidence: 99%
“…However, in a practical situation, it may not be possible to vary all the system parameters independently to the extent manifested in Equation (166) as follows by rearranging Equation (145) and by substituting us/eg for vg and eg + eg for 1 ' . This implies that;…”
Section: Practical Procedures For Scale-downmentioning
confidence: 99%
“…In the radial direction, there was no change in heat transfer coefficient except very near to the wall. A short critical review of many experimental studies was reported by Zabrodsky et al [1976]. They commented that heat transfer coefficient for an internal surface is higher than the external wall at low gas flow rates.…”
Section: Particle Sphericitymentioning
confidence: 99%
“…Regarding the effect of particle thermal conductivity, Zabrodsky et al [1976] noted that for short residence time of the packet of particles on the heat transfer surface that the heat wave penetrates only the particles next to the wall and a change in the thermal conductivity of particle could be important for heat transfer.…”
Section: Particle Thermophysical Propertiesmentioning
confidence: 99%